2017
DOI: 10.1002/mabi.201700147
|View full text |Cite
|
Sign up to set email alerts
|

Electroactive 3D Scaffolds Based on Silk Fibroin and Water‐Borne Polyaniline for Skeletal Muscle Tissue Engineering

Abstract: Silk fibroin (SF) with good biocompatibility and degradability has great potential for tissue engineering. However, the SF based scaffolds lack the electroactivity to regulate the myogenic differentiation for the regeneration of muscle tissue, which is sensitive to electrical signal. Herein, a series of electroactive biodegradable scaffolds based on SF and water-soluble conductive poly(aniline-co-N-(4-sulfophenyl) aniline) (PASA) via a green method for skeletal muscle tissue engineering are designed. SF/PASA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 58 publications
1
24
0
Order By: Relevance
“…The results showed that dually crosslinked GelMA-alginate bioinks with 8% (w/v) alginate promoted the myotube formation compared to other bioinks. This result is consistent with the previous report that scaffolds for myoblast culture require a compression modulus of at least 200 kPa to tolerate cell-induced deformation in the differentiation process [24,25]. High mechanical strength of dually crosslinked GelMA-8% (w/v) alginate bioinks supported cell-cell contact and thereby cell-cell fusion during the differentiation process more as compared to other bioinks.…”
Section: Resultssupporting
confidence: 91%
“…The results showed that dually crosslinked GelMA-alginate bioinks with 8% (w/v) alginate promoted the myotube formation compared to other bioinks. This result is consistent with the previous report that scaffolds for myoblast culture require a compression modulus of at least 200 kPa to tolerate cell-induced deformation in the differentiation process [24,25]. High mechanical strength of dually crosslinked GelMA-8% (w/v) alginate bioinks supported cell-cell contact and thereby cell-cell fusion during the differentiation process more as compared to other bioinks.…”
Section: Resultssupporting
confidence: 91%
“…The protein‐based scaffolds hold promise in tissue engineering, since the extracelluar matrix is composed of the natural proteins and glycosaminoglycans . Therefore, many natural proteins have been applied to fabricate tissue engineering scaffold, such as collagen and silk fibroin (SF) . SF, which is synthesized by an enormous variety of insect and spider species, has received attentions as potential biomedical purposes in the field of tissue engineering and drug delivery system since of its impressive mechanical strength, low inflammation reaction, and degradation properties .…”
Section: Introductionmentioning
confidence: 99%
“… Electroconductive Du et al [ 43 ] Poly (citric acid-octanediol-polyethylene glycol)(PCE)-graphene (PCEG) nanocomposite Murine C2C12 myoblasts In vivo Addition of reduced graphene oxide (RGO) improved scaffold mechanical properties and electrical conductivity. Addition of RGO increased scaffold myofiber and capillary density in vivo Zhang et al [ 84 ] SF/PASA: Silk fibroin with poly(aniline‐co‐N‐(4‐sulfophenyl) aniline) Murine L929 fibroblast and C2C12 myoblasts In vitro Characterisation of scaffold electroconductivity and biodegradability. Increasing PASA content enhanced myogenic differentiation of C2C12 myoblasts Ostrovidov et al [ 69 ] Gelatin-polyaniline (PANI) electrospun nanofibers Murine C2C12 myoblastis In vitro The addition of PANI increased nanofiber electroconductivity by 10 4 S/cm.…”
Section: Scaffold Use For Skeletal Muscle Engineeringmentioning
confidence: 99%